2018
DOI: 10.1007/s12253-018-0383-y
|View full text |Cite
|
Sign up to set email alerts
|

Boost Irradiation Integrated to Whole Brain Radiotherapy in the Management of Brain Metastases

Abstract: Our retrospective analysis aimed to evaluate the clinical value of dose intensification schemes: WBRT and consecutive, delayed, or simultaneous integrated boost (SIB) in brain metastasis (BM) management. Clinical data and overall survival (OS) of 468 patients with BM from various primaries treated with 10 × 3 Gy WBRT (n = 195), WBRT+ 10 × 2 Gy boost (n = 125), or simultaneously 15 × 2.2 Gy WBRT+0.7 Gy boost (n = 148) during a 6-year period were statistically analysed. Significant difference in OS could be dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…However, WBRT alone only extends the median survival time by up to 6 months (9,10). WBRT plus in-field radiotherapy boost is an effective strategy for improving the intracranial control rate (ICR) and selecting patients who could experience significant survival benefits (11)(12)(13)(14)(15)(16)(17). WBRT followed by SRS (WBRT + SRS) and WBRT combined with simultaneous integrated boost (SIB) are the two main boost schemes for BM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, WBRT alone only extends the median survival time by up to 6 months (9,10). WBRT plus in-field radiotherapy boost is an effective strategy for improving the intracranial control rate (ICR) and selecting patients who could experience significant survival benefits (11)(12)(13)(14)(15)(16)(17). WBRT followed by SRS (WBRT + SRS) and WBRT combined with simultaneous integrated boost (SIB) are the two main boost schemes for BM.…”
Section: Introductionmentioning
confidence: 99%
“…A dosimetric study showed that WBRT combined with SIB (WBRT + SIB) could satisfy the target dose and protect the surrounding normal tissues such as the hippocampus (19). Several studies have also reported that WBRT + SIB significantly improves ICR and survival compared to WBRT alone (14,16,20). However, it is unclear whether WBRT + SIB can improve efficacy and reduce toxicity compared to WBRT + SRS.…”
Section: Introductionmentioning
confidence: 99%
“…In the Australian cohort reported by Awad et al using VMAT to apply hippocampal avoidance WBRT to 30 Gy in 15 fractions and a SIB to 50 Gy to median two BM, the median OS was 9.4 months 26. In addition, in a recent analysis on radiation techniques in BM from various tumors, Dobi et al reported dose-escalated radiotherapy to be able to improve survival in patients with BM from MM from 3.2 months after WBRT only to 6.5 months after dose-escalated treatment 31. In accordance to those prior publications, the analysis of the imaging response in every individual BM in the standard versus experimental arm in our trial revealed the SIB in the experimental arm to result in a significantly improved local control of the individual BM.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that intensive treatment for metastatic lesions, including surgery and stereotactic radiosurgery (SRS), combined with WBRT might improve local control of oligo-brain metastases [23,24]. Dobi et al have reported that dose escalation to brain metastatic lesion can achieve better local control and survival, even among patients with extracranial metastasis [25]. To reduce the risk of cognitive decline and improve clinical outcomes, attempts have been made at adding simultaneous integrated boost (SIB) to HS-WBRT.…”
Section: Plos Onementioning
confidence: 99%